2019
DOI: 10.1016/j.appet.2018.11.014
|View full text |Cite
|
Sign up to set email alerts
|

A serial mediation model of the relationship between alexithymia and BMI: The role of negative affect, negative urgency and emotional eating

Abstract: Difficulty identifying and describing emotions (alexithymia) has been related to impulsiveness and negative affect, emotional eating and obesity. However, previous research findings concerning the relationship between alexithymia and obesity have been mixed and inconsistent, raising the possibility that the relationship is indirect and mediated by multiple unknown factors. The aim of the study was to comprehensively explore the potential pathways between alexithymia and obesity via a novel theoretical model, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 73 publications
3
18
0
3
Order By: Relevance
“…Overeating has also been described as an outcome of a maladaptive approach with negative and not-mentalized emotions, particularly anxiety, preceding uncontrolled food intake episodes in individuals that are overweight [61,64]. In the model of Pink et al [27], it was suggested that alexithymia, which is only indirectly predictive of variation in BMI, would predispose people to higher vulnerability to depressive and anxious symptoms, which would determine impulsive eating behaviors.…”
Section: Discussion Of Cross-sectional Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Overeating has also been described as an outcome of a maladaptive approach with negative and not-mentalized emotions, particularly anxiety, preceding uncontrolled food intake episodes in individuals that are overweight [61,64]. In the model of Pink et al [27], it was suggested that alexithymia, which is only indirectly predictive of variation in BMI, would predispose people to higher vulnerability to depressive and anxious symptoms, which would determine impulsive eating behaviors.…”
Section: Discussion Of Cross-sectional Studiesmentioning
confidence: 99%
“…Indeed, alongside genetic and environmental factors [23], emotional dysregulation and impairment of interoceptive awareness have been explored as risk factors for overeating and obesity [24,25]. Moreover, in the general population, emotional dysregulation has been associated with high BMI and maladaptive eating behaviors (i.e., overeating; [26,27]). Accordingly, several studies showed significant emotional regulation differences between individuals with excessive body weight and normal weight [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…The first factor, that accounted for 43% of the variance, included items 2, 3, 4, 5, 6, 8 y 9, and seems to reflect those behaviors most directly related to EE, according to previous research: food intake triggered by emotions [1] (items 5, 6 and 8), the preference for certain foods [14] (items 2, 3, 4, 6 and 9) and the difficulty in controlling eating [49] (items 2, 3, 4, 8 and 9). EE not only involves eating in response to certain emotions, but also it has been suggested the implication of some executive mechanisms, like impulsivity and the inability to modulate emotional responses [66]. Besides, EE is related to unhealthy food choices [12].…”
Section: Discussionmentioning
confidence: 99%
“…Third, the lack of standardized tests to account for the concurrent validity of the EEQ. Fourth, a comparative study about EEQ between clinical and non-clinical population would be needed, and a greater exploration across Spanish non-clinical samples would also be beneficial, since models of EE could differ between student and general population samples [66]. Finally, although there is a large body of research and empirical studies about EE, both on clinical samples and normal population, this construct is not as simple as is often assumed.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between stress and emotional eating has also been shown to be modulated by Body Mass Index (BMI; Nguyen-Rodriguez, Chou, Unger, & Spruijt-Metz, 2008;Tchanturia et al, 2012;Torres & Nowson, 2007). Additionally, alexithymia has been related to higher levels of obesity, emotional eating, and more in general to impulsivity and negative affect (Casagrande, Boncompagni, Forte, Guarino, & Favieri, 2019;Pink, Lee, Price, & Williams, 2019). It has been suggested that higher alexithymia reduces the ability to identify emotional states and to distinguish them from internal signals of hunger and satiety, therefore leading individuals to regulate their emotions through food intake (Pink et al, 2019;Tan & Chow, 2014), increasing their BMI (Casagrande et al, 2019;Tan & Chow, 2014;Taylor, Parker, Bagby, & Bourke, 1996).…”
Section: Introductionmentioning
confidence: 99%